INNOWACJE METODOLOGICZNE – ZASTOSOWANIE INNOWACYJNYCH TECHNIK ELICYTACJI W BADANIU KOMPETENCJI KOLOKACYJNEJ - Targońska, Joanna (Neofilolog, 2018)
Research on collocational competence, which is a component of lexical competence, is part of more general research on the acquisition of vocabulary. The methodology adopted in such research continues to evolve. The present article overviews some elicitation techniques for measuring the acquisition of collocations which have been used so far, focusing on their weaknesses. Another focus of the article is innovative and unconventional techniques of elicitation, which are not only an effective measure of the growth of students’ receptive and productive collocational competence, but also a means of raising their collocational awareness.